Pengaruh Tool Path Dan Feed Rate Pada Proses Mesin CNC Milling Router 3 Axis Dengan Material Acrylic - Wijayanto, Dwi; , Bambang Waluyo Febriantoko, ST., MT; , Agus Dwi Anggono, ST, M.Eng, Ph.D (2016)
The aim of study is to determine the effect of tool path and feed rate variations on a flat surface of acrylic material machined by CNC milling Router 3 axis, on the surface roughness in unit of Roughness average (Ra). This study used acrylic materials and CNC milling machine 3 axis Router with mach3 control. Machining process was conducted by varying the feed tool path and feed rate. Roughness Tester Type TR200 with ISO standards was used for surface roughness testing. The results showed that the lower feed rate used in the process the lower value of surface roughness was. The level of roughness with variations of zig - zag, parallel spiral and one way tool path and feed rate of 200,300,400 mm/min produced the level of roughness between the N7 until N8.The lowest value of surface roughness in the parallel spiral tool path with a feed rate of 200 mm/min was at 1.178 μm with an average value of Roughness Average ( Ra ) was 1.675 μm , whereas the highest value of surface roughness on the one way tool path with a feed rate of 400 mm / min was at 2.555 μm with an average value of Roughness average ( Ra ) was 2.482 μm. Hence the highest level of fineness resulted from this study that was the spiral tool path parallel with feed rate of 200 mm/min.